A comparison of urinary bladder weight in male and female mice across five models of diabetes and obesity - Erdogan, Betül R.; Michel, Martina B.; Matthes, Jan; Castañeda, Tamara R.; Christen, Urs; Arioglu-Inan, Ebru; Michel, Martin C.; Pautz, Andrea (Frontiers in Pharmacology, 2023)
Diabetes often leads to lower urinary tract dysfunction. The most frequently assessed parameter of urinary bladder dysfunction in animal models of diabetes is an enlargement of the bladder, which is consistently observed in type 1 and less consistently in type 2 diabetes. The vast majority of studies on bladder weight in animal models of diabetes and obesity has been performed in males, and no studies have directly compared this outcome parameter between sexes. Therefore, we have compared bladder weight and bladder/body weight ratio in five mouse models of obesity and diabetes (RIP-LCMV, db/db, ob/ob (two studies), insulin receptor substrate 2 (IRS2) knock-out mice and mice on a high-fat diet; pre-specified secondary analysis of a previously reported study). In a pooled analysis of the control groups of all studies, females exhibited slightly lower glucose levels, lower body weight, and lower bladder weight, but bladder/body weight ratio was similar in both sexes (0.957 vs. 0.986 mg/g, mean difference 0.029 [-0.06; 0.118]). Among the six diabetic/obese groups, bladder/body weight ratio was similar in both sexes in three but smaller in female mice in three other groups. The mRNA expression of a panel of genes implied in the pathophysiology of bladder enlargement and/or fibrosis and inflammation did not differ systematically between sexes. We conclude that sex differences in diabetes/obesity-associated bladder enlargement may be model dependent.